Combined filter material for emission reduction in an internal combustion engine fired with bioliquids - Walberer, Julian; Meiller, Martin; Daschner, Robert; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2019)
In Europe, air pollution, especially NOx and particulate matter, leads to a tightening of the limit values for several combustion processes, including stationary as well as mobile applications. This trend is also affecting several biomass applications. Due to this, Fraunhofer UMSICHT has developed a filter material which reduces pollutants such as NOx, SO2 and particulate matter by combining filtration and selective catalytic reduction in one process step. The core part of the filter is a ceramic filter candle, which is used for common dust separation. The ceramic filter material is activated with modified catalysts to enable selective catalytic reduction (SCR) at low temperatures (150 – 200 °C). This paper describes the activation of the filter material with cooper-zeolite-catalysts (Cu-ZSM) and the evaluation via SCR-test-bench. A test run demonstrates the practical suitability using exhaust gas from a compression ignition engine operating with biofuels.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Catalyst; Emission; Filtration; NOx emission; Pyrolysis oil